Penn State Group of Japanese English Teachers Thank You Letter - Cloene I. Marson::::::; Janice A. Boge:::::: (1973)
A letter from a group of Japanese English Teachers thanking members of the Oxnard City Council for allowing them to visit and tour Oxnard and Port Hueneme as part of an Exchange Program.